Carbons, Ionic Liquids, and Quinones for Electrochemical Capacitors - Díaz-Delgado, Raül; Doherty, Andrew P. (Frontiers in Materials, 2016)
Carbons are the main electrode materials used in electrochemical capacitors, which are electrochemical energy storage devices with high power densities and long cycling lifetimes. However, increasing their energy density will improve their potential for commercial implementation. In this regard, the use of high surface area carbons and high voltage electrolytes are well known strategies to increase the attainable energy density, and lately ionic liquids have been explored as promising alternatives to current state of the art acetonitrile-based electrolytes. Also, in terms of safety and sustainability ionic liquids are attractive electrolyte materials for electrochemical capacitors. In addition, it has been shown that the matching of the carbon pore size with the electrolyte ion size further increases the attainable electric double layer (EDL) capacitance and energy density. The use of pseudocapacitive reactions can significantly increase the attainable energy density, and quinonic-based materials offer a potentially sustainable and cost effective research avenue for both the electrode and the electrolyte. This perspective will provide an overview of the current state of the art research on electrochemical capacitors based on combinations of carbons, ionic liquids and quinonic compounds, highlighting performances and challenges and discussing possible future research avenues. In this regard, current interest is mainly focused on strategies which may ultimately lead to commercially competitive sustainable high performance electrochemical capacitors for different applications including those requiring mechanical flexibility and biocompatibility.